Decision Making Methodology for Heat Sink Material Selection Using a Compromise Ranking and Outranking Method under Fuzzy Environment - Loganathan, Arulmurugan; Mani, Ilangkumaran (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
This paper proposes judicious selection of heat sink materials by extensive evaluation under consideration of numerous alternative materials and evaluation criteria. This enhances the reliability and life of modern electronic devices. Thermal management of electronic devices relies on stabilizing the component temperature at an acceptable level. A hierarchical decision making framework structure based on novel hybrid fuzzy set theory combined with multi-criteria decision-making (MCDM) model is formed. A fuzzy analytic hierarchical process (FAHP) is more realistic to use linguistic terms to describe the expectation value, perception value and important weight of evaluation criteria. This study comprises six alternatives and seven criteria such as thermal conductivity, density, specific heat, melting point, latent heat of fusion, thermal expansion and cost. The results obtained from FAHP-TOPSIS and FAHP- VIKOR is compared with each other. These results help the designer to choose the apt heat sink material for designing and developing electronic packages.